Pemberdayaan Masyarakat Desa Bacin Melalui Optimalisasi Pengelolaan Sampah Plastik - Meilani Vianti Putri; Rima Nurul Hidayati (Universitas Negeri Semarang, 2025)
The problem of plastic waste is a serious issue in society, including in Bacin Village, Bae District, Kudus Regency. The purpose of community service is to empower PKK mothers in processing plastic waste, making craft skills, and developing an entrepreneurial spirit. The service method used is training with the target community of PKK Village mothers. In this service, the community turns plastic waste into products with sales value. In addition, the activities also integrate Pancasila values, such as cooperation, social justice, and concern for the environment. The results of the training showed high enthusiasm from participants, increased skills, and the potential for developing a creative economy in Bacin Village. With this program, it is hoped that sustainable solutions can be created to reduce plastic waste and increase community income. With the existence of products with sales value, it can increase the entrepreneurial spirit of the community.